2013
DOI: 10.1063/1.4793487
|View full text |Cite
|
Sign up to set email alerts
|

Conditions for a carrier multiplication in amorphous-selenium based photodetector

Abstract: Amorphous selenium is a promising candidate for high sensitivity photodetector due to its unique carrier multiplication phenomenon. More than 10 carriers can be generated per incident photon, which leads to high photo-conversion efficiency of 1000% that allows real-time imaging in dark ambient. However, application of this effect has been limited to specific devices due to the lack in material characterization. In this article, mechanism of carrier multiplication has been clarified using time-of-flight seconda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…In addition, the I-V curve at voltage 100-350 V shows a relatively small current increase, while it shifts to a rapid increase at voltages above 350 V. This tendency in the I-V curve suggests that there are two or more factors that limit the I-V characteristics. A possible explanation is that the emission current is limited by transport of photogenerated holes at voltages lower than 350 V, then it shifts into "avalanche mode" when the applied voltage is above 350 V. In our previous study, carrier multiplication at applied voltage around 340 V is reported for a 2 m thick film in a contact current -applied voltage measurement [7].…”
Section: Resultsmentioning
confidence: 96%
See 3 more Smart Citations
“…In addition, the I-V curve at voltage 100-350 V shows a relatively small current increase, while it shifts to a rapid increase at voltages above 350 V. This tendency in the I-V curve suggests that there are two or more factors that limit the I-V characteristics. A possible explanation is that the emission current is limited by transport of photogenerated holes at voltages lower than 350 V, then it shifts into "avalanche mode" when the applied voltage is above 350 V. In our previous study, carrier multiplication at applied voltage around 340 V is reported for a 2 m thick film in a contact current -applied voltage measurement [7].…”
Section: Resultsmentioning
confidence: 96%
“…A lightly N-doped diamond with extraction voltage of 400 V was selected in this study, to apply high voltages of up to 350 V between the anode and the cathode. This high voltage was necessary to induce carrier multiplication in a-Se [7].…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…With a negative electron affmity surface and M-I-V type emission [3], N-doped diamond emitter should provide sufficient emission current for wide dynamic range, as well as small dispersion angle for high spatial resolution. Furthermore, high-sensitivity photo detection has been demonstrated using carrier multiplication in a-Se [4]. Emission current-applied voltage (I V) characteristics of the detector are compared between photodetectors with different set-up configurations in order to evaluate the sensitivity enhancement due to internal signal multiplication.…”
Section: Introductionmentioning
confidence: 99%